EMI shielding fabric and preparation method thereof
By adsorbing aramid nanofibers on the surface of high-temperature resistant fabrics and performing electroless nickel plating treatment, the problem of insufficient interface bonding and shielding performance of high-temperature resistant fabrics is solved, and the preparation of flexible conductive high-temperature resistant EMI shielding fabrics is realized, with excellent electromagnetic shielding Performance and multiple performance improvements.
Patent Information
- Application Number
- CN202411488805.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The prior art is difficult to effectively improve the interface bonding and shielding performance of high-temperature resistant fabrics, resulting in poor electromagnetic interference shielding effect.
Through self-assembly technology, aramid nanofibers are adsorbed on the surface of high-temperature resistant fabrics, and ultrasonic treatment and sodium borohydride solution activation treatment, and finally palladium-free electroless nickel plating to prepare flexible conductive high-temperature resistant EMI shielding fabrics with excellent electromagnetic shielding performance. .
The interface bonding force of high-temperature resistant fabrics has been significantly improved, and the shielding performance has been significantly improved. It can effectively solve the electromagnetic interference problem between electronic components, and at the same time it has excellent flexibility, heat resistance and corrosion resistance.
Smart Images

Figure CN119433970A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electromagnetic shielding materials and conductive composite fabrics, and specifically relates to an EMI shielding fabric and a preparation method thereof. Background Art
[0002] Layer-by-layer (LBL) self-assembly technology is an efficient method to build composite films on the surface of solid or other flexible substrates. This technology mainly uses the electrostatic interaction between substances. Through a sequential deposition process, the substrate is given a specific charge and immersed in a solution of opposite charge for self-assembly. In this process, polydimethyldiallylammonium chloride (PDDA) is a cationic electrolyte to achieve surface modification.
[0003] With the promotion and popularization of the fifth generation of communications (5G), the problem of electromagnetic wave pollution has attracted widespread attention. Long-term exposure to electromagnetic radiation may cause harm to human health. Therefore, the demand for high-performance electromagnetic interference shielding (EMI) fabrics has become more urgent. Conductive composite fabrics have significant application potential in EMI shielding fabrics due to their light weight, flexibility and easy processing.
[0004] Patent CN207820462U prepares a high-temperature resistant and highly elastic conductive EMI SMT foam through a high-viscosity glue process. However, multiple metal plating layers may damage the flexibility of the substrate and increase the weight of the composite fabric; using viscous glue as a bonding method may cause it to fall off during later use, which will seriously affect the shielding performance and cannot meet the future requirements for EMI shielding materials to be lightweight, flexible and have good EMI performance.
[0005] According to existing literature reports, the performance of conductive composite fabrics depends largely on the strength of the interface between the matrix and the filler. For some high-temperature resistant fabrics, such as aramid fiber cloth, its chemical inertness and smooth surface limit the chemical bonding and mechanical interlocking with other materials, resulting in weak interfacial bonding and poor shielding performance of the conductive aramid composite material. In response to the above problems, the prior art generally modifies the high-temperature resistant fiber cloth with low surface chemical activity through surface treatment methods to enhance the interfacial interaction with other materials. For example, chemical etching, plasma treatment and other methods can improve the interfacial bonding of the matrix to a certain extent, but the degree of chemical modification of the above methods is difficult to control.
[0006] Based on this, a controllable modification method for high temperature resistant fabrics with weak interfacial bonding strength is needed in the art. Summary of the invention
[0007] Based on the above problems, the purpose of this application is to overcome the defects of the prior art and provide an EMI shielding fabric and a preparation method thereof, so that it can shield electromagnetic wave pollution.
[0008] To this end, the first technical solution of the present application discloses a method for preparing an EMI shielding fabric, comprising: self-assembling a high temperature resistant fabric to obtain a flexible high temperature resistant fabric and then chemically depositing a metal nickel layer to obtain the EMI shielding fabric.
[0009] Furthermore, the self-assembly is provided with positive charge by polydimethyldiallyl ammonium chloride solution and negative charge by aramid nanofiber dispersion.
[0010] Furthermore, the aramid nanofiber dispersion is prepared by dispersing aramid nanofibers, wherein the aramid nanofibers are one or more of para-aramid yarn fibers, para-aramid staple fibers, para-aramid fabric fibers, para-aramid fibrils, para-aramid pulp, meta-aramid staple fibers, meta-aramid fibrils, and meta-aramid filaments.
[0011] Furthermore, the self-assembly is to immerse the high temperature resistant fabric in a polydimethyldiallyl ammonium chloride solution to obtain a positively charged fabric, and then immerse it in an aramid nanofiber dispersion to obtain a negatively charged fabric, and cycle the process until a flexible high temperature resistant fabric with stably adsorbed aramid nanofibers is obtained.
[0012] Furthermore, the high temperature resistant fabric is any one or more of asbestos fiber cloth, glass fiber cloth, aramid fiber cloth, carbon fiber cloth, polytetrafluoro fiber cloth, polyimide fiber cloth, polyethersulfone fiber cloth, and silicone fiber cloth.
[0013] Furthermore, the method for chemically depositing the metal nickel layer is as follows: subjecting the flexible high temperature resistant fabric to ultrasonic treatment with a nickel ion solution-1, activation treatment with a sodium borohydride solution, and then chemically nickel plating the surface of the fabric with a chemical nickel plating solution.
[0014] Furthermore, the chemical nickel plating solution is obtained by adding sodium citrate and sodium hypophosphite to the nickel ion-containing solution-2 and then adjusting the pH to alkaline.
[0015] Furthermore, the ultrasonic treatment power is 40-240w.
[0016] And, the EMI shielding fabric prepared by the above preparation method.
[0017] The second technical solution of the present application discloses the application of the above-mentioned EMI shielding fabric in shielding electromagnetic waves.
[0018] The present invention uses a flexible high temperature resistant fiber cloth as a matrix, and uses a self-assembly technology: a positively charged PDDA solution and a negatively charged ANF dispersion liquid are circulated for treatment. With the help of electrostatic interaction, the chemical inertness of the aramid fabric itself can be improved without destroying the mechanical properties of the aramid fabric itself, thereby improving the chemical bonding force and mechanical interlocking between it and other materials. Afterwards, the fiber membrane is activated by ultrasonic treatment and sodium borohydride solution treatment, and finally, nickel is chemically plated on the surface of the ANFs adsorbed high temperature resistant fabric through a palladium-free chemical plating process. The prepared high temperature resistant flexible fabric has excellent flexibility, heat resistance, corrosion resistance and efficient shielding effect; the thickness, conductivity and shielding properties of the material are controlled by adjusting the process parameters. The method is easy to operate, economical and environmentally friendly. The porous structure of the formed flexible conductive high temperature resistant EMI shielding fabric and the nickel coating on the surface make the material have excellent electromagnetic shielding properties, which can solve the problem of mutual interference between electronic components. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 These are SEM images of the original fabric, the ANFs-absorbed flexible high-temperature resistant fabric, and the flexible conductive high-temperature resistant EMI shielding fabric of Example 1 of the present invention.
[0020] Figure 2 These are the XRD spectra of the original fiber cloth, the ANFs-adsorbed flexible high-temperature resistant fabric, and the flexible conductive high-temperature resistant EMI shielding fabric of Example 1 of the present invention.
[0021] Figure 3 These are the TGA and DTG curves of the original fiber cloth, the ANFs-absorbed flexible high-temperature resistant fabric, and the flexible conductive high-temperature resistant EMI shielding fabric of Example 1 of the present invention.
[0022] Figure 4 This is the environmental stability of the flexible conductive high temperature resistant EMI shielding fabric of Example 1 of the present invention.
[0023] Figure 5 The conductive properties and shielding properties of the flexible conductive high temperature resistant EMI shielding fabric of Example 1 of the present invention. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Unless otherwise specifically stated, the relative arrangement, numerical expressions and numerical values of the parts and steps set forth in these embodiments do not limit the scope of the present application. At the same time, it should be understood that, for ease of description, the sizes of the various parts shown in the accompanying drawings are not drawn according to the actual proportional relationship. The technology, method and equipment known to those of ordinary skill in the relevant field may not be discussed in detail, but in appropriate cases, the technology, method and equipment should be considered as a part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, so that once a certain item is defined in an accompanying drawing, it does not need to be further discussed in subsequent drawings.
[0026] The first embodiment of the present application discloses a method for preparing an EMI shielding fabric, comprising: self-assembling a high temperature resistant fabric to obtain a flexible high temperature resistant fabric, and then chemically depositing a metal nickel layer to obtain the EMI shielding fabric.
[0027] In this embodiment, the high temperature resistant fabric is any one or more of asbestos fiber cloth, glass fiber cloth, aramid fiber cloth, carbon fiber cloth, polytetrafluoro fiber cloth, polyimide fiber cloth, polyethersulfone fiber cloth, silicone fiber cloth, which can withstand high temperatures above 500°C, but generally has chemical inertness and a smooth surface, thereby limiting the chemical bonding and mechanical interlocking with other materials, resulting in weak interface bonding and poor shielding performance. The purpose of this application is to provide a technical means for improving the bonding strength of high temperature resistant fabrics.
[0028] In this embodiment, the self-assembly is an efficient method for constructing composite films on the surface of solid or other flexible substrates. This technology mainly uses the electrostatic interaction between substances. Through a sequential deposition process, the substrate is given a specific charge and immersed in a solution of opposite charge for self-assembly.
[0029] In this embodiment, the self-assembly is provided with positive charge by polydimethyldiallyl ammonium chloride solution (PDDA solution), and negative charge by aramid nanofiber (ANF) dispersion. Preferably, the concentration of the PDDA solution is 1-5wt%, and the aramid nanofiber dispersion is prepared according to the following steps:
[0030] S1. Potassium hydroxide and substance B are mixed at a ratio of (0.3-3.0) g:20 mL, where substance B is one or more of deionized water, ethanol and methanol, to obtain solution A;
[0031] S2. Solution A was mixed with dimethyl sulfoxide in a ratio of 20 mL:500 mL to obtain a mixed system B;
[0032] S3. Add aramid fiber to the mixed system B at a ratio of 2g:520mL, and continue stirring at 40-80°C and 500-1200r / min. The stirring speed is 800-1200r / min and the stirring time is 1-7 days to obtain an aramid nanofiber dispersion. It should be noted that in order to shorten the experimental period, this step can be subjected to heat treatment.
[0033] The nanofibers are any one or more of para-aramid yarn fibers, para-aramid chopped fibers, para-aramid fabric fibers, para-aramid fibrils or para-aramid pulp, meta-aramid chopped fibers, meta-aramid fibrils, and meta-aramid filaments.
[0034] In this embodiment, the specific step of the self-assembly is to immerse the fabric in a polydimethyldiallyl ammonium chloride solution to obtain a positively charged fabric, and then immerse it in an aramid nanofiber dispersion to obtain a negatively charged fabric, and repeat this process until a flexible high temperature resistant fabric with stably adsorbed aramid nanofibers is obtained. For this reason, the preferred number of cycles in this application is 1-10 times, and the immersion time is 10 to 120 minutes.
[0035] It should be noted that, since aramid fabrics generally have a smooth surface and are chemically inert, they have poor bonding ability with other materials and weak interfacial interaction forces. Therefore, the present application assembles aramid nanofibers (ANFs) (in the form of aramid nanofiber dispersion) on the fabric surface through self-assembly technology, because ANFs are obtained by peeling off macroscopic aramid fibers in polar solvents, so they are negatively charged; in order to assemble ANFs on the fabric surface, electrostatic interactions are required, and PDDA is a cationic electrolyte with a positive charge, so a layer of PDDA and a layer of ANF can be self-assembled, thereby stably adsorbed on the fabric surface, and finally a layer of ANFs is dipped, and the charge of the entire fabric comes from the ANFs on the surface, which is a negative charge. The entire self-assembly process is a surface modification treatment method for aramid fabrics. Finally, the surface of the aramid fabric adsorbed with ANFs becomes rough, which is conducive to the subsequent better bonding of metal nickel ions and the self-assembled fabric. In addition, the metal nickel ions are positively charged, and the fabric adsorbed with ANF is negatively charged. Through electrostatic interaction, they can also combine more firmly with the aramid fabric, thus obtaining an aramid fabric with high conductivity and high EMI shielding effect.
[0036] In a further embodiment, the obtained flexible high temperature resistant fabric that stably adsorbs ANF is treated with a chemically deposited metal nickel layer. The specific treatment method is to ultrasonically treat the flexible high temperature resistant fabric with a nickel ion solution-1, activate it with a sodium borohydride solution, and then chemically nickel-plate its surface using a chemical nickel plating solution.
[0037] In a further embodiment, the ultrasonic treatment causes the microjets generated in the ultrasonic bath to form new active points on the surface of the nanofiber flexible film, promoting the oxidation of hydroxyl groups on the surface of the fiber membrane to form carboxyl groups, thereby increasing the oxygen-containing polar functional groups on the surface of the fiber membrane, which helps to improve the wettability of the fiber membrane surface, improve the surface activity of the fiber membrane, and help the carboxyl groups on the surface of the fiber membrane to react with Ni 2+ Contact, so that it undergoes a coordination reaction to form a coordination bond -COO-Ni, thereby modifying and modifying the metal ions, stabilizing the metal ions on the ligand molecules, and improving the binding force between the fiber membrane and the metal ions. In order to achieve the above purpose, the ultrasonic treatment power is 40-240w.
[0038] In this embodiment, the nickel ion solution-1 is obtained by dissolving a nickel salt. The preferred nickel salt in this application is nickel chloride hexahydrate. Specifically, nickel chloride hexahydrate is added to deionized water and mixed until it is completely dissolved. When nickel chloride hexahydrate is used as the nickel salt, the applicant determines through gradient experiments that the concentration of the nickel chloride solution is 0.5-40 g / L, preferably 0.5, 1, 4, 8, 10, 20, 40 g / L, and the corresponding nickel ion concentration is 0.05wt%-4wt%.
[0039] In a further embodiment, after the ultrasonic treatment, a sodium borohydride solution activation treatment is performed, the purpose of which is to better reduce the metal nickel ions on the surface of the fiber membrane in the subsequent chemical nickel plating process. Compared with the palladium activation process commonly used in the prior art, the present application uses sodium borohydride to activate the fiber membrane, which can significantly save and reduce costs.
[0040] In this embodiment, the preparation method of the chemical nickel plating solution is to add sodium citrate and sodium hypophosphite to the nickel ion-containing solution-2 and then adjust the pH to alkaline.
[0041] The preparation method of the nickel ion solution-2 is consistent with that of the nickel ion solution-1, wherein, in terms of mass percentage concentration, Ni 2+ The content is preferably 6wt%-18wt% of the nickel ion solution-2.
[0042] In a further embodiment, the purpose of adding sodium citrate and sodium hypophosphite is to improve the quality of the coating and ensure the stability of the electroplating process. Sodium citrate can form a stable complex with nickel ions, which can prevent nickel ions from precipitating or being reduced in the electrolyte, thereby helping nickel ions to stably exist in the electrolyte. At the same time, sodium citrate can promote the formation of deposits and enhance the adhesion between the deposits and the substrate. In addition, the chemical plating system containing sodium hypophosphite is environmentally friendly. In order to ensure the high conductivity of the resulting coating and form a coating with a low phosphorus content, it is selected to perform chemical nickel plating in an alkaline environment. Therefore, the pH range can be 8 to 14. The present application is preferably pH = 10, and for this reason, the addition ratio of nickel ion solution to sodium citrate and sodium hypophosphite is preferably 1.9:1:1.7.
[0043] It should be noted that in the process of selecting nickel as a conductive filler in the prior art, metallic nickel is generally directly blended and compounded with a matrix material. However, this composite method will lead to uneven dispersion of nickel nanoparticles. The nickel nanoparticles and the matrix material are only combined together by physical forces, which will also cause problems with shielding performance and stability. Alternatively, the traditional palladium activation process is used to chemically deposit nickel, which will result in high costs and cause environmental pollution.
[0044] It is understandable that the surface of the high temperature resistant fabric is wet; therefore, it needs to be dried, and the drying temperature is 40-80°C. In addition, in order to further increase the corrosion resistance of the high temperature resistant fabric after chemical nickel plating, the surface can also be dip-coated with polydimethylsiloxane encapsulation liquid. This is because the polydimethylsiloxane encapsulation liquid dip-coating can make the coating have good bonding force with the substrate, prevent the conductive layer from falling off while maintaining the flexibility of the nanofiber membrane, making it super-hydrophobic, and can further enhance the corrosion resistance of the conductive film. The polydimethylsiloxane encapsulation liquid is preferably prepared by the following method: the polydimethylsiloxane base liquid is mixed with the solvent in a ratio of 1:1 to 1:10. The solvent is one or more of xylene, n-hexane and n-decane.
[0045] The technical effects of the present invention will be more clearly described below in conjunction with the accompanying drawings and specific embodiments.
[0046] Example 1 Preparation of EMI shielding fabric
[0047] S1. Pretreatment: Wash the aramid fiber cloth (high temperature resistant flexible fabric) alternately in acetone and deionized water, dry it and set it aside;
[0048] S2. Weigh polydimethyldiallylammonium chloride (PDDA), add deionized water to a beaker, and stir to obtain a colorless solution;
[0049] S3. Self-assembly: The cleaned high temperature resistant flexible fabric in S1 was immersed in the 3wt% PDDA solution prepared in S2 for 10 min, then washed with deionized water and dried to obtain a high temperature resistant flexible fabric with positive charge; then immersed in aramid fiber nano dispersion for 10 min, washed with deionized water to obtain a high temperature resistant flexible fabric loaded with negatively charged aramid nanofibers (ANFs); the self-assembly process was repeated four times, and after sufficient drying, a stable high temperature resistant fabric adsorbing ANFs was obtained;
[0050] S4. The high temperature resistant fabric stably adsorbing ANFs was immersed in a solution containing nickel ions at a concentration of 0.5 g / L for ultrasonic treatment, washed with deionized water, dried at 80°C and immersed in a sodium borohydride solution for activation, and after washing and drying, 3 g of nickel chloride was weighed and added to 100 mL of deionized water and mixed until completely dissolved (Ni 2+ The content is 9wt%), 3g of sodium citrate and sodium hypophosphite are added in sequence to form a mixture containing Ni 2+ A green transparent solution is prepared, and then a 20wt% sodium hydroxide solution is used to adjust the pH value of the mixed solution to 10.0. The high temperature resistant fabric is immersed in a chemical nickel plating solution for chemical nickel plating, and a flexible conductive high temperature resistant EMI shielding fabric is obtained after drying.
[0051] Comparative Example 1 Preparation of EMI shielding fabric
[0052] The preparation method is the same as that in Example 1, except that the concentration of the nickel ion-containing solution-1 in step S4 is changed to 1 g / L, 4 g / L, 8 g / L, 10 g / L, 20 g / L, and 40 g / L.
[0053] Test Example 1 Characterization Experiment
[0054] The EMI shielding fabric prepared in Example 1 was subjected to characterization tests. Figure 1 This is a SEM image of a flexible conductive high temperature resistant EMI shielding fabric. It can be observed that the gaps between the aramid fibers are filled and completely covered by the assembled ANFs coating, but the fiber skeleton of the fiber cloth can still be observed. After chemical nickel plating, the surface of the fiber cloth becomes rougher, and a continuous and dense metal nickel coating is formed on the surface of the fabric, but the fiber skeleton of the fiber cloth can still be observed. Figure 2 Figure 1 is the XRD spectrum of the original fiber cloth (aramid fiber cloth) and the flexible conductive high temperature resistant EMI shielding fabric prepared in Example 1. Compared with the XRD spectrum of the original fiber cloth, the peaks of the XRD spectrum of the flexible conductive high temperature resistant EMI shielding fabric at 44.8°, 51.9° and 76.3° belong to the characteristic peaks of metallic nickel, which confirms that Ni 2+ The successful reduction of shows that the flexible conductive high temperature resistant EMI shielding fabric has been successfully prepared.
[0055] Test Example 2 Stability Test
[0056] The flexible conductive high temperature resistant EMI shielding fabric prepared in Example 1 was used as an electromagnetic shielding material to test thermal stability and environmental stability. Figure 3 These are the TGA and DTG curves of the original fiber cloth and the flexible conductive high temperature resistant EMI shielding fabric. From its DTG data, it can be seen that the decomposition of the original fiber cloth mainly occurs between 488℃ and 636℃, and the maximum decomposition rate temperature is around 558℃, which shows that the original fiber cloth itself has excellent thermal stability. After chemical nickel plating, it can be seen that the maximum decomposition rate temperature of the flexible conductive high temperature resistant EMI shielding fabric is about 553℃, and its thermal decomposition temperature has no significant change compared with the original fiber cloth. This shows that the flexible conductive nanofiber membrane has good thermal stability. The flexible conductive high temperature resistant EMI shielding fabric was placed in a 150℃ blast oven for one week to evaluate the high temperature resistance of the nickel coating; the flexible conductive high temperature resistant EMI shielding fabric was immersed in 10wt% HCl, 10wt% NaOH and 5wt% NaCl solution for 48 hours for corrosion resistance test to evaluate the corrosion resistance of the nickel coating.
[0057] Figure 4 This is a graph showing the changes in the microscopic morphology and sheet resistance of the EMI shielding fabric after the environmental stability test. The results show that after a week of high-temperature treatment at 150°C, the surface morphology of the flexible conductive high-temperature resistant EMI shielding fabric has hardly changed, and the original spherical particles are still maintained, and the overall morphology of the fiber can also be observed. In addition, the unit mass has not changed, and the sheet resistance has increased slightly compared with the initial value, and it still has good conductivity. In addition, it can be observed that in an acidic environment, the nickel coating on the surface is corroded to a certain extent, obvious gaps appear, and the sheet resistance increases significantly; after alkaline treatment, a small range of flaky structures appear on the surface, and the sheet resistance increases slightly; while in a saline environment, the overall morphology and sheet resistance are almost unaffected. Based on the above analysis, the prepared flexible conductive high-temperature resistant EMI shielding fabric has relatively weak resistance to acidic environments, but has good stability in high temperature, alkaline and salt environments.
[0058] Test Example 3: Shielding Test
[0059] The flexible conductive high temperature resistant EMI shielding fabric prepared in Example 1 was used as an electromagnetic shielding material to test its conductivity and shielding performance under different concentrations of nickel ion solution-1. The specific steps are as follows:
[0060] The flexible conductive high temperature resistant EMI shielding fabric is cut into discs with a diameter of 12mm. The conductivity of the conductive performance is tested using a four-probe, and the EMI shielding performance is tested using a vector network analyzer with a measurement frequency range of 8.2-12.4GHz. When the flexible conductive high temperature resistant EMI shielding fabric is used as a shielding material, its shielding mechanism mainly includes three aspects: first, the reflection attenuation of electromagnetic waves on the surface of the material; second, the further attenuation caused by the absorption of electromagnetic waves penetrating the surface of the material inside the material; and finally, the multiple reflection attenuation of electromagnetic waves inside the material. The electromagnetic shielding effectiveness (EMI SE) is calculated by the following formula: SE T =SE A +SE R+ SE M , where SE T is the total electromagnetic shielding efficiency, SE A is the efficiency of electromagnetic wave absorption loss, SE R Indicates the efficiency of electromagnetic wave reflection loss, SE M It is the efficiency of multiple reflection loss of electromagnetic waves.
[0061] Figure 5 This is a graph showing the changes in conductivity and shielding performance under different concentrations of nickel-ion solution-1. When there is no metallic nickel load, the surface of the original fiber cloth is insulating and has almost no shielding performance against electromagnetic waves. When the concentration of nickel-ion solution-1 is as low as 0.5g / L, the shielding performance of the flexible conductive high-temperature resistant EMI shielding fabric within the test frequency range is about 27.9dB. As the concentration of nickel-ion solution-1 increases, the value of EMI SE will also increase. In addition, the maximum shielding effectiveness of the prepared flexible conductive high-temperature resistant EMI shielding fabric can reach 100.5dB, which means that nearly 99.99% of electromagnetic waves are shielded by the composite fabric.
[0062] In summary, the present invention provides a flexible conductive high-temperature resistant EMI shielding fabric based on LBL technology and a preparation method thereof. In this method, a positively charged PDDA solution is first adsorbed on the surface of the high-temperature resistant fabric, and then the positively charged fabric is immersed in a pre-prepared ANF dispersion to obtain a high-temperature resistant fabric that stably adsorbs ANFs; then, the high-temperature resistant fabric is pretreated by ultrasonic treatment, and then the fabric is activated by sodium borohydride solution treatment, and finally, nickel is chemically plated on the surface of the high-temperature resistant fabric adsorbing ANFs through a palladium-free chemical plating process, and a flexible conductive high-temperature resistant EMI shielding fabric with excellent EMI shielding performance is successfully prepared; through electrostatic interaction, ANFs can significantly increase the roughness of the surface of the high-temperature resistant fabric, thereby significantly improving the interfacial interaction force between the substrate and the coating; the high-temperature resistant fabric after ultrasonic treatment can provide more active sites, which promotes the oxidation of hydroxyl groups on the surface of the fabric to form carboxyl groups. The increase in the number of polar functional groups is beneficial to the wettability of the high-temperature resistant fabric, that is, it helps the carboxyl groups on the surface of the high-temperature resistant plant to react with Ni 2+ The method is easy to operate, economical and environmentally friendly, and the porous structure of the formed flexible conductive high temperature resistant EMI shielding fabric and the nickel coating on the surface give the material excellent electromagnetic shielding performance, which can solve the problem of mutual interference between electronic components.
[0063] The above embodiments are only used to illustrate the technical solutions of the present invention, but the protection scope of the present invention is not limited thereto. The embodiments of the present invention and the features in the embodiments can be arbitrarily combined with each other without conflict. Any technician familiar with the technical field can easily think of changes or replacements within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing an EMI shielding fabric, characterized in that: include: The high temperature resistant fabric is self-assembled to obtain a flexible high temperature resistant fabric, and then a metal nickel layer is chemically deposited to obtain an EMI shielding fabric.
2. The preparation method according to claim 1, characterized in that: The self-assembly is provided with positive charge by polydimethyldiallyl ammonium chloride solution, and negative charge by aramid nanofiber dispersion.
3. The preparation method according to claim 2, characterized in that: The aramid nanofiber dispersion is prepared by dispersing aramid nanofibers in the aramid nanofiber dispersion, wherein the aramid nanofibers are one or more of para-aramid yarn fibers, para-aramid staple fibers, para-aramid fabric fibers, para-aramid fibrils, para-aramid pulp, meta-aramid staple fibers, meta-aramid fibrils, and meta-aramid filaments.
4. The preparation method according to claim 1, characterized in that: The self-assembly is to immerse the high temperature resistant fabric in a polydimethyldiallyl ammonium chloride solution to obtain a positively charged fabric, and then immerse it in an aramid nanofiber suspension to obtain a negatively charged fabric, and repeat this process until a flexible high temperature resistant fabric with stably adsorbed aramid nanofibers is obtained.
5. The preparation method according to claim 1, characterized in that: The high temperature resistant fabric is any one or more of asbestos fiber cloth, glass fiber cloth, aramid fiber cloth, carbon fiber cloth, polytetrafluoro fiber cloth, polyimide fiber cloth, polyethersulfone fiber cloth, and silicone fiber cloth.
6. The preparation method according to claim 1, characterized in that: The method for chemically depositing the metal nickel layer comprises: subjecting the flexible high temperature resistant fabric to ultrasonic treatment with a nickel ion solution, activation treatment with a sodium borohydride solution, and then chemically plating the surface of the fabric with a chemical nickel plating solution.
7. The preparation method according to claim 6, characterized in that: The chemical nickel plating solution is obtained by adding sodium citrate and sodium hypophosphite to the nickel ion-containing solution-2 and adjusting the pH to be alkaline.
8. The preparation method according to claim 6, characterized in that: The ultrasonic treatment power is 40-240w.
9. An EMI shielding fabric prepared according to any one of the preparation methods of claims 1-8.
10. Use of the EMI shielding fabric according to claim 9 in shielding electromagnetic waves.
Citation Information
Patent Citations
High temperature resistant high -elastic electrically conductive electromagnetic shield SMT steeps cottonly
CN207820462U
Palladium-free activation chemical nickel-plating method for electromagnetic shielding polyphenylene sulfide fiber
CN105200761A
Preparation method of nano aramid film based on vacuum auxiliary layer-by-layer self-assembly
CN108084468A
Cited By
Bamboo charcoal fiber cloth-based composite material as well as preparation method and application thereof
CN121951910A